2021
DOI: 10.3390/ijms22063010
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Metabolomics in Forensic Toxicology and Forensic Medicine

Abstract: Forensic toxicology and forensic medicine are unique among all other medical fields because of their essential legal impact, especially in civil and criminal cases. New high-throughput technologies, borrowed from chemistry and physics, have proven that metabolomics, the youngest of the “omics sciences”, could be one of the most powerful tools for monitoring changes in forensic disciplines. Metabolomics is a particular method that allows for the measurement of metabolic changes in a multicellular system using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 96 publications
(115 reference statements)
0
32
0
1
Order By: Relevance
“…Recent pioneering works regarding the consideration of mi-RNAs [135] or the entity of metabolites (metabolome) [136,137] to prove lethal TBIs in a forensic setting should be further explored. Using a combination of six different mi-RNAs, it was possible to discriminate TBI cases from controls that were free of neurological symptoms [135].…”
Section: The Present and Future Of Post-mortem Tbi-related Biomarkersmentioning
confidence: 99%
“…Recent pioneering works regarding the consideration of mi-RNAs [135] or the entity of metabolites (metabolome) [136,137] to prove lethal TBIs in a forensic setting should be further explored. Using a combination of six different mi-RNAs, it was possible to discriminate TBI cases from controls that were free of neurological symptoms [135].…”
Section: The Present and Future Of Post-mortem Tbi-related Biomarkersmentioning
confidence: 99%
“…Toxicometabolomics has grown far beyond its initial preclinical and clinical applications. A rising number of studies showed that metabolomics is a powerful tool for elucidating biochemical modes of action and toxicological effects of a wide range of toxic compounds in a variety of toxicology domains, including food safety [ 137 , 138 ], environmental toxicology [ 139 , 140 ], and forensic toxicology [ 141 , 142 ]. Metabolomics has also recently gained attention as a novel tool in regulatory toxicology [ 143 ].…”
Section: Metabolomics: a New Route In Toxicological Researchmentioning
confidence: 99%
“…Quantitative measurement of circulating small-molecule metabolites that may participate in disease pathogenesis [ 34 ] may improve diagnosis, unravel appropriate therapeutic targets, and enable a more precise prognosis of disease outcome [ 35 ]. Metabolomics studies have successfully identified biomarkers for diagnosis, progression, and treatment response for age-related diseases such as cancer, diabetes, and autoimmune diseases [ 36 , 37 , 38 , 39 ]. A recent study has reported the presence of an abundant amount of coagulation-related protein Kininogen-1 in EVs, such as exosomes isolated from COVID-19 patients, and suggested that exosomes may act as a reserve of Kininogen-1 [ 40 ].…”
Section: Introductionmentioning
confidence: 99%